2009
DOI: 10.1007/s11664-009-0876-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Current Direction on the Cu-Ni Cross-Interaction in Cu/Sn/Ni Diffusion Couples

Abstract: The influence of current direction on the Cu-Ni cross-interaction in the Cu/Sn/Ni joint configuration was investigated in this study. During current stressing, an electric current towards or away from the Ni-side of Cu/Sn/Ni was imposed at 150°C. It was observed that the (Cu,Ni) 6 Sn 5 ternary compound was the dominant reaction product at both interfaces, and its growth at the Ni-side strongly depended upon the direction and magnitude of the electron flow. When the electron flow was towards the Ni-side, more C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 43 publications
(57 reference statements)
3
21
0
Order By: Relevance
“…14 We hypothesized that this increase resulted from more Ni being capable of migration to the Cu side during soldering because the distance between Cu and Ni was reduced by half, to 50 lm, in this present study. Additionally, there were (Cu,Ni) 6 Sn 5 compounds uniformly scattered throughout the entire Sn matrix, as shown in Fig.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…14 We hypothesized that this increase resulted from more Ni being capable of migration to the Cu side during soldering because the distance between Cu and Ni was reduced by half, to 50 lm, in this present study. Additionally, there were (Cu,Ni) 6 Sn 5 compounds uniformly scattered throughout the entire Sn matrix, as shown in Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Once J em Cu is comparable to J chem Cu , they will cancel each other, resulting in the amount of Cu on the Ni side (N Cu ) reaching a so-called dynamic equilibrium. From our preliminary study, 14 N Cu [or (Cu,Ni) 6 Sn 5 ] was found to remain nearly unchanged over time under 10 4 A/cm 2 stressing at 150°C. This finding suggested that J chem Cu is completely inhibited by the J em Cu induced by 10 4 A/cm 2 current stress.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations